ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH (Periode 2012-2014) - Syaidina Efri Saputra; Emrinaldi Nur DP; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to compare the financial performance of conventional banking with Islamic banking in the period 2012-2014 by using financial ratios. Financial ratios used consisted of Capital (CAR), Assets (NPL/NPF), Earnings (ROA, NIM/NOI and BOPO), and Liquiduty (LDR/FDR). The population in this research is 118 companies conventional banking and 11 companies Islamic banking which are listed Bank of Indonesia during the period of 2012-2014 while the amount of the research samples are 20 banks, is 10 conventional banks and 10 islamic banks. This study using hypothesis testing the